Seberapa Besar Kontribusi Tingkat Pendidikan Ibu terhadap Prestasi Belajar Matematika Siswa pada Masa Pandemi Covid-19? - Wijayanti, Asri Nabila; Isrokatun, I; Sunarya, Dede Tatang (Jurnal Pena Ilmiah, 2021)
This research aims to: (1) To find out whether there is a relationship between mother’s education level and students’ mathematics learning achievement. (2) To find out how much the mother’s education level contributes to students’ mathematics achievement. This research uses quantitative survey methods using correlation research model. The subject of this study was 5th grade students of SD Negeri Ciluluk II with a total of 55 students, with random sampling techniques. Data collection techniques using questionnaires (polls). Data analysis techniques use product moment correlation, simple regression and SPSS programs. The results showed that (1) There is a positive relationship in the low category as indicated by the r value of 0,341 and a significant value is indicated by the α value of the mother’s level of education on mathematics learning achievemet of 0,001. (2) The contribution of the influence of mother’s education level to students’ mathematics learning achievement is 11,6%. While 88,4% is influenced by other variables.